Producción y propagación de neutrones en jets de microcuásares - Escobar, Gastón Javier (2018)
A usual investigation line to address the study of jets nature and composition is to determine the energetics of the relativistic particles populations which are present in the jet, and the electromagnetic radiation emitted by them. The neutron component, originated in situ through interactions of relativistic protons with matter or radiation, has not been studied in microquasars. The neutrons, when decaying or interacting with matter or radiation fields, introduce new relativistic electron and proton sources, distributing the latter populations along the jet. Since neutrons do not interact with magnetic fields, their dynamics are distinct to that of charged particles. This allows neutrons to escape from the acceleration region easier than other particles, taking an energy fraction away of the system. In this work we introduce the relativistic neutron component in the study of energetics of relativistic particles of microquasar jets. We model the spectral energy distributions with a One-Zone approximation to solve the appropriate transport equations.